Mothers’ attitudes towards their own presence during invasive procedures on their children - Karapınar, Bülent; Yılmaz, Deniz; Egemen, Ayten (The Turkish Journal of Pediatrics, 2005)
This study assessed of the preferences 742 mothers regarding their own presence during invasive procedures performed on their children. The relationships between socio-demographical characteristics and preferences of the mothers and disease characteristics of the children were examined. A mother’s desire to be present was found to increase with decreasing invasiveness of the procedure as well as with increasing analgesia and sedation provided. The desire to be present was higher in young mothers with higher socio-economic levels and educational backgrounds, with younger children and with children who had undergone prior recurrent interventions. This study demonstrated that most of the mothers preferred to be present during the procedure, and that the ratio of mothers willing to do so increased significantly if the children were sedated. The results suggested that pediatricians can improve the quality of service and physician-patient-family relationship by taking mothers’ preferences into consideration.